2020
DOI: 10.1101/2020.02.28.969261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thecis-regulatory codes of response to combined heat and drought stress inArabidopsis thaliana

Abstract: Plants respond to their environment by dynamically modulating gene expression. A powerful approach for understanding how these responses are regulated is to integrate information about cis-regulatory elements (CREs) into models called cis-regulatory codes. Transcriptional response to combined stress is typically not the sum of the responses to the individual stresses. However, cis-regulatory codes underlying combined stress response have not been established. Here we modeled transcriptional response to single … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
3
1
Order By: Relevance
“…3 B ). The importance of exonic features relative to upstream and downstream regions observed across grasses for cold in this study is the opposite of the pattern reported in a recent study of heat- and drought-responsive genes in Arabidopsis using k-mer features ( 36 ). The involvement of UTRs in transcriptional regulation was also observed in a study predicting mRNA expression levels from DNA sequence features in maize and sorghum ( 24 ).…”
Section: Discussioncontrasting
confidence: 99%
“…3 B ). The importance of exonic features relative to upstream and downstream regions observed across grasses for cold in this study is the opposite of the pattern reported in a recent study of heat- and drought-responsive genes in Arabidopsis using k-mer features ( 36 ). The involvement of UTRs in transcriptional regulation was also observed in a study predicting mRNA expression levels from DNA sequence features in maize and sorghum ( 24 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The full set (all motifs associated with the sets of all up- or down- regulated genes or specific co-expression clusters) of motifs identified for cold or heat responsive expression (above) were used and we determined the presence/absence for each motif within different sets of search spaces (Figure 3A) to assess how the use of different potential ‘promoter’ regions would affect model performance. The approach previously described by Zou et al (Zou et al, 2011; Uygun et al, 2017, 2019; Azodi et al, 2020a) was implemented to utilize the motif features to predict whether genes will exhibit cold- or heat-responsive expression. For each co-expression cluster, we compared the genes in the cluster to an equivalent number of genes that are expressed, but not classified as DE; and ran the model 100 times using all motifs, or only retaining the most highly enriched motifs (top 30, 50, 100 or 200) followed by calculation of the AUROC (see Methods for details; Figure 4; Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning approaches have provided new and powerful ways for understanding and predicting gene expression in plants (Azodi et al, 2020b; Wang et al, 2020b; Washburn et al, 2019). These approaches have been used to predict expression levels (Washburn et al, 2019; Sartor et al, 2019), regulatory architecture (Mejía-Guerra and Buckler, 2019), as well as gene expression responses to abiotic stress (Zou et al, 2011; Uygun et al, 2017, 2019; Azodi et al, 2020a; Schwarz et al, 2020). These studies highlight the potential to develop predictive models that use putative cis-regulatory motifs to predict gene expression responses to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has increasingly more often been applied to genomics research (Golicz et al 2020). For example,machine learning has been used to predict gene expression levels from genomic sequence data (Azodi, Lloyd, and Shiu, n.d.). Machine learning has also been used in the biomedical field to diagnose disease (Kourou et al 2015).…”
Section: Introductionmentioning
confidence: 99%